The welfare state in post-industrial society : a global perspective - Hendricks, Jon , 1943-; Powell, Jason L. , 1971- (Springer, 2009)
In recent years, major forces have reshaped social welfare policies and practices across the globe. This book is a comparative analysis of the effect of globalization on the international welfare state. It discusses many countries and includes case studies